Systemic sclerosis: Current concepts in pathogenesis and therapeutic aspects of dermatological manifestations - Vishalakshi Viswanath; Meghana M Phiske; Vinay V Gopalani (Wolters Kluwer Medknow Publications, 2013)
Systemic sclerosis (SSc) is a chronic, multisystem connective tissue disease with protean clinical manifestations. Recent advances in understanding the pathogenic mechanisms have led to development of target-oriented and vasomodulatory drugs which play a pivotal role in treating various dermatological manifestations. An exhaustive literature search was done using Medline, Embase, and Cochrane library to review the recent concepts regarding pathogenesis and evidence-based treatment of salient dermatological manifestations. The concept of shared genetic risk factors for the development of autoimmune diseases is seen in SSc. It is divided into fibroproliferative and inflammatory groups based on genome-wide molecular profiling. Genetic, infectious, and environmental factors play a key role; vascular injury, fibrosis, and immune activation are the chief pathogenic factors. Vitamin D deficiency has been documented in SSc and correlates with the severity of skin involvement. Skin sclerosis, Raynaud's phenomenon (RP) with digital vasculopathies, pigmentation, calcinosis, and leg ulcers affect the patient's quality of life. Immunosuppressives, biologicals, and hematopoietic stem cell transplantation are efficacious in skin sclerosis. Endothelin A receptor antagonists, calcium-channel blockers, angiotensin receptor inhibitors, prostacyclin analogs, and phosphodiesterase type 5 (PDE-5) inhibitors are the mainstay in RP and digital vasculopathies. Pigmentation in SSc has been attributed to melanogenic potential of endothelin-1 (ET-1); the role of ET 1 antagonists and vitamin D analogs needs to be investigated. Sexual dysfunction in both male and female patients has been attributed to vasculopathy and fibrosis, wherein PDE-5 inhibitors are found to be useful. The future concepts of treating SSc may be based on the gene expression signature.